Chart of Accounts : A Critical Element of the Public Financial Management Framework - Pattanayak, Sailendra; Cooper, Julie (Washington, D.C. : International Monetary Fund, 2011)
This technical note and manual (TNM) addresses the following main issues: -- Discusses the purpose of a chart of accounts and its importance in public financial management -- Discusses stakeholder needs in a typical public financial management framework that need to be reflected in a chart of accounts -- Discusses the role of chart of accounts in budgetary and financial accounting -- Discusses the relation between the chart of accounts and IFMIS -- Explains key steps for identifying data requirements and structures for developing a chart of accounts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet